Meteorological Dominance and Short-Term Responses: Discourse Network Analysis on the 2025 Cilacap Landslide in Online Media - Suwarno; Nurul Hasfi; Kristiyawanto (Ikatan Sarjana Komunikasi Indonesia, 2026)
The 2025 Cilacap landslide occurred in a region with an expired disaster risk assessment document. This study aims to analyze the discourse network structure in online media reports on the 2025 Cilacap landslide using discourse network analysis (DNA) to reveal how actors collaborate in narratives about causes and solutions and their implications for the public agenda and mitigation policies. The analysis unit used 37 news articles from online media verified by the Press Council on November 13-28, 2025, and analyzed using DNA 3.0.11 and Visone 2.28.2. The data were annotated by actors, organizations, and concepts, divided into cause data (65 statements from 27 articles) and solution data (16 statements from 10 articles), and then calculated for centrality (degree, betweenness, closeness). Results show that high-intensity rainfall achieved the highest degree centrality (16.129 %) among causal factors and was supported by a strong coalition of national agencies (BNPB, BMKG, Geological Agency). Anthropogenic and governance-related factors appeared but remained peripheral (centrality < 3 %). In the solution network, temporary shelters (huntara) and BNPB were most central (betweenness centrality 37.931% and 62.069%, respectively). At the same time, long-term measures (reforestation, spatial planning, technology-based early warning systems) were mentioned but isolated (betweenness centrality 0%). The study reveals a media discourse heavily reliant on official national sources, leading to meteorological explanations and short-term emergency responses that overshadow structural mitigation narratives. This study is limited to textual analysis of news reports; future research may complement it with interviews or production-side analysis.